TRPV2 POLYMORPHISMS CHANGE THE RISK OF TYPE 2 DIABETES - HASHIMOTO THYROIDITIS COMORBIDITY - Arikan, F. Bulut; Ozdemir, F. A.; Sen, D.; Erdem, S.; Yorubulut, S.; Dogan, H.; Keskin, L. (Editura Acad Romane, 2020)
Context. Thyroid disorders are common in diabetics and related to severe diabetic complications. TRPV2 ion channels have crucial functions in insulin secretion and glucose metabolism which have an important role in the pathophysiology of diabetes. Also, they have a significant effect on various immunological events that are involved in the HT pathophysiology. Objective. This study aimed to investigate rs14039 and rs4792742 polymorphisms of the TRPV2 ion channels in type 2 diabetes mellitus (T2DM, n=100) Hashimoto thyroiditis (HT, n=70) and comorbid T2DM and HT (T2DM+HT, n=100) patients and control (n=100). Design. Case-control study Subject and Methods. RT-PCR genotyping was used to determine rs14039 and rs4792742 polymorphisms with DNA samples of subjects and appropriate primer and probes. Besides, required biochemical analyses were performed. Results. It was determined that the frequencies of the rs14039 GG homozygote polymorphic genotype and the G allele were significantly higher in T2DM+HT patients compared to the control (p=0.03 and p=0.01, respectively) and that especially the GG genotype increases the risk of T2DM+HT 3.046-fold (p=0.01, OR=3.046). It was detected that the GG genotype increased the risk of HT 2.54-fold (p=0.05, OR=2.541). TRPV2 rs4792742 polymorphisms reduce the risk of HT and T2DM+HT comorbidity almost by half and have a protective effect against HT and T2DM+HT. Conclusion. The rs14039 GG genotype of the TRPV2 gene significantly increases the risks of development of T2DM+HT and HT disorders, may have a significant role in the pathophysiology of these diseases, also leading to predisposition for their development. Conversely, rs4792742 polymorphic genotypes have a strong protective effect against the HT and T2DM+HT comorbidity.
Keywords: TRPV2; Type 2 Diabetes Mellitus; Hashimoto Thyroiditis; Polymorphisms